2002
DOI: 10.1002/j.2161-1912.2002.tb00480.x
|View full text |Cite
|
Sign up to set email alerts
|

White Racial Identity and White Racial Consciousness: Similarities, Differences, and Recommendations

Abstract: To dispel apparent confusion, White racial identity and White racial consciousness are described and contrasted in terms of theoretical conceptualization and measures used. It is recommended that priority be given to the validation of existing or new measurement instruments to provide a sound basis for future findings.Para disipar la confusion aparente, la identidad racial Blanca, y el conocirniento racial Blanco, se describen y son contrastados en terminos de sus conceptos teoricos y las medidas empleadas. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Helms's (, ) theory of WRID has focused on how Whites perceive and interact with people of color, with little description about how Whites may define their own and others' WRIs (Leach et al, ; Miller & Fellows, ). The findings from our study extend understanding of how Whites who demonstrate characteristics of the autonomy status develop and make meaning of their WRIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helms's (, ) theory of WRID has focused on how Whites perceive and interact with people of color, with little description about how Whites may define their own and others' WRIs (Leach et al, ; Miller & Fellows, ). The findings from our study extend understanding of how Whites who demonstrate characteristics of the autonomy status develop and make meaning of their WRIs.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, critiques have emerged regarding Helms's (, ) model. Scholars have noted limitations in the model's ability to concretely operationalize the experiences, lifestyles, and perceptions of Whites (Leach, Behrens, & LaFleur, ; Miller & Fellows, ). For instance, Rowe () criticized the autonomy status as a simplistic description of Whiteness that was developed “in the absence of supporting evidence” (p. 242).…”
mentioning
confidence: 99%
“…Rowe et al (1994) identified two status constellations of racial attitudes within the White Racial Consciousness model: (a) unachieved White racial consciousness, which is characterized by a lack of White identity awareness, exploration, and/or commitment and (b) achieved White racial consciousness status, which is characterized by awareness and exploration of race and about racial concerns and commitment to particular racial attitudes. Changes in racial attitudes result from life experiences that generate cognitive dissonance, and resulting exploration and resolution of that dissonance (Leach, Behrens, & LaFleur, 2002; Rowe et al, 1994). White racial consciousness is important because previous research and theory agree that ally action is dependent on White racial consciousness, in terms of recognizing awareness of the unearned benefits (Case, 2012; Michael & Conger, 2009; Reason, Roosa Millar, & Scales, 2005; Smith & Redington, 2010) related to being White, in contrast to being a person of color.…”
mentioning
confidence: 99%
“…Janet Helms's (1990, 1995, 2014) model of White racial identity development (WRID) is one of the most widely used models in teaching, counseling, and research (Ford & Orlandella, 2015; Hays et al, 2021; Helms, 2014; Turnage‐Butterbaugh, 2017). Counselor educators have used Helms's (1995) model to shape curriculum and assess and support White students’ racial identity development (Brown et al, 1996; Malott et al, 2015), stressing the importance of facilitating learners’ WRID in order to increase multicultural competency (Brown et al, 1996; A. Johnson & Williams, 2015; Leach et al, 2002). Understanding WRID can provide direction for personal and client racial identity growth (A. Johnson & Williams, 2015; Utsey et al, 2002), and Sue et al (2019) contended that movement toward a nonracist White identity is essential for Whites to conduct effective multicultural counseling.…”
mentioning
confidence: 99%